Informing environmental problems through field analysis: Toward a community landscape theory of pro-environmental behavior. Issue 4 (8th August 2017) - Mainzer, Stephen; Luloff, A. E.
Abstract: The physical and social environments influence individual values, perceptions, and actions from which community emerges. These relationships outline a multi-level transdisciplinary framework of interactions that inform human behavior. This article seeks to accomplish three things: (1) to construct a rationale for unifying commonalities among field-based concepts of behavior, landscape, and community; (2) to describe a transdisciplinary field theory-based model of pro-environmental behavior; and (3) to provide a hypothetical application. Finally, we present a community landscape model of pro-environmental behavior as a framework for addressing complex and wicked environmental problems that require transdisciplinary approaches.